2019
DOI: 10.1111/jace.16333
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and characterization of IR‐transparent Fe2+ doped MgAl2O4 ceramics

Abstract: Initial investigations on the preparation of highly transparent Fe 2+ :MgAl 2 O 4 ceramics using nanopowders synthesized in a laser plume were carried out. For the first time, dense Fe 2+ :MgAl 2 O 4 ceramics with high transmission in the mid-IR range were fabricated at a temperature as low as 1300°C and with a short sintering time (1 hour). The obtained Fe 2+ :MgAl 2 O 4 ceramics contain a secondary (MgO) 0.91 (FeO) 0.09 phase with a low wt% content, causing a substantial decrease in transmittance in the visi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…In this work, we aim to fabricate and study the microstructure, vibronic and optical properties of novel transparent ceramics and GCs based on Fe 2+ :MgAl2O4 spinel crystals. Previously, the authors from the Institute of Electrophysics UD RAS reported the development of transparent Fe 2+ :MgAl2O4 ceramics [49][50][51]. The obtained ceramics [49][50][51] contained secondary oxide phase of (MgO)0.91(FeO)0.09 causing a substantial decrease in transmittance in the visible range.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this work, we aim to fabricate and study the microstructure, vibronic and optical properties of novel transparent ceramics and GCs based on Fe 2+ :MgAl2O4 spinel crystals. Previously, the authors from the Institute of Electrophysics UD RAS reported the development of transparent Fe 2+ :MgAl2O4 ceramics [49][50][51]. The obtained ceramics [49][50][51] contained secondary oxide phase of (MgO)0.91(FeO)0.09 causing a substantial decrease in transmittance in the visible range.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, the authors from the Institute of Electrophysics UD RAS reported the development of transparent Fe 2+ :MgAl2O4 ceramics [49][50][51]. The obtained ceramics [49][50][51] contained secondary oxide phase of (MgO)0.91(FeO)0.09 causing a substantial decrease in transmittance in the visible range. In those ceramics Fe 3+ ions are located both in the primary spi-4 nel phase Fe:MgAl2O4 and in the secondary phase Fe:MgO, which results in a very low determined GSA cross sections of Fe 2+ ions in tetrahedral site symmetry [49].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that iron doping concentrations as small as 0.1 mol.% yields strong NIR absorption peaks substantially larger than the ones observed in the spectrum shown in Figure 2B suggesting a significantly lower impurity concentration within our injection molded MAS. [ 39 , 40 ] For a quantitative analysis of the impurity concentration we characterized the HIP treated MAS using X‐ray fluorescence (XRF) as shown in Figure 2C . We found weak signals for chromium and iron impurities, most likely due to minor abrasion during compounding and injection molding.…”
Section: Preparation and Processing Of Thermoplastic Mgal2o4 Nanocomp...mentioning
confidence: 99%
“…The fluorescent materials with Fe as activator ions have drawn a lot of attention in recent years owing to the potential application in red phosphors, fluorescence thermometry, and laser technology. [1][2][3] The Fe atom with electron arrangement of [Ar]3d 6 4s 2 is easy to lose two or three electrons to form Fe 2+ or Fe 3+ ion. The Fe 2+ -doped ZnS, ZnSe, and MgAl 2 O 4 have been widely explored as tunable mid-infrared (3−5 μm) laser materials.…”
Section: Introductionmentioning
confidence: 99%